Kolaborasi Siswa Dan Sekolah Dalam Upaya Pengendalian Kenakalan Remaja - Rinaldi, Kasmanto (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2023)
Juvenile delinquency is a social phenomenon that involves behavior that does not comply with the norms and rules that apply in society. Juvenile delinquency has a negative impact on individuals, families and society. One of the factors that can affect the level of juvenile delinquency is the school environment. Collaboration between students and schools is crucial in controlling juvenile delinquency. In criminological studies, collaboration between students and schools can be an effective strategy in controlling juvenile delinquency. Schools act as educational institutions that can provide a holistic approach to prevention and intervention. The problem that occurred at SMAN 2 XIII Koto Kampar was that there was a lot of juvenile delinquency committed by students due to a lack of knowledge about juvenile delinquency. This service is carried out with the aim of forming students' understanding, especially students of SMAN 2 XIII Koto Kampar regarding juvenile delinquency and its effects, and an introduction regarding the importance of collaboration between students and schools as controlling juvenile delinquency. This service method is carried out by carrying out the preparation stages and the implementation stages of socialization. The results found in this service are that students understand the impact of juvenile delinquency and the urgency of collaboration in controlling juvenile delinquency and follow socialization properly.